Compositional Trends and Eruptive Cycles at Mount St Helens - Hopson, Clifford; Melson, William (Geoscience Canada, 1990)
Summary The 40,000-year eruptive history of Mount St.Helens reveals an overall compositional trend from rhyodacite to andésite, with basalt at -1.9and -1.6 ka. A cyclic eruption pattern is super-imposed on this trend. Cycles comprised arepose interval, when compositional and thermal gradients developed in the underlying magma body, followed by an eruption intervalin which progressive tapping of magma be-headed these gradients. Recovery of gradients varied with duration of the ensuing repose period. Eruption sequences follow the pattern: (1) eruptive progression from Pli-nian eruptions to dome growth accompanied by pyroclastic flows and tephra, followed (insome cases) by lava flows punctuated bypyroclastic outbursts; (2) a minéralogie pro-gression from hydrous Fe-Mg phenocrysts(hb, cm, bi) toward pyroxenes; (3) a magmatlc compositional progression from rhyodaciteor dacite to andésite. Progressions 1 and 2 stem mainly from volatile gradients in the magma reservoir whereas progression 3 (andto some extent 2) reflects gradients of melt composition and crystal content. Three eruption cycles within the last 4,000 years follow this pattern. Earlier cycles are probable but only dimly perceived, mainly from the partial record of tephras and pyroclastic flows.